PENGEMBANGAN SAPI POTONG BERBASIS SUMBERDAYA LAHAN DAN KELEMBAGAAN DI KABUPATEN GORONTALO - Azhar, Muhammad Nur; Gandasasmita, Komarsa; Abdullah, Luki (Jurnal Manajemen Pembangunan Daerah, 2014)
ABSTRACT National beef consumption continues to increase from year to year, which is characterized by increase the number of requests. This condition is not accompanied by a number of domestic production is unable to meet the needs of national beef. The Government alternative measures of addressing these issues is making import policy. Therefore, the government continues to increase beef production through the national programs and work together with local governments. This study aims to: identify patterns of effective and efficientbeef cattle development, identifying suitability and carrying capacity of the land and to formulate development strategies beef cattle in Gorontalodistrict. The primary data obtained by surveys, direct observation, and interviews (agencies and related institutions) by purposive sampling method. The analytical method used for each objective are: literature review, analysis of Geographic Information Systems (GIS), SWOT analysis and Quantitative Strategic Planning Matrix (QSPM). From the results of the literature review, the development pattern of the area is the effective and efficient development. GIS analysis results show the suitability of the ecological environment of beef cattle reached 178 455 ha (81% of the area of Gorontalo district, the largest potential area for beef cattle development is Asparaga Subdistrict arround 11 232 ha and forage carrying capacity index of the largest fodder is Tolangohula subdistrict arround 39,2. From the SWOT strategy formulation obtained strengthening planning reinforcement development area, strengthening human resources officials and farmers, strengthening institutional breeders,  strengthening inter-agency coordination, strengthening the production infrastructure, accelerating adoption of production technologies, strengtheningmarketing institutional and socialization development of beef cattle. Key words:    Beef cattle, land suitability, beef cattle development strategy, Gorontalo District  ABSTRAK Konsumsi daging sapi nasional terus mengalami peningkatan dari tahun ke tahun yang ditandai dengan peningkatan jumlah permintaan yang meningkat. Kondisi ini tidak dibarengi dengan jumlah produksi dalam negeri yang tidak mampu memenuhi kebutuhan daging sapi nasional. Langkah alternatif pemerintah dalam mengatasi persoalan tersebut dengan membuat kebijakan impor. Oleh karena itu pemerintah terus berupaya meningkatkan produksi daging sapi nasional melalui program-program dan bersinergi dengan pemerintah daerah. Penelitian ini bertujuan untuk: mengindentifikasi pola pengembangan sapi potong yang efektif dan efesien, mengindentifikasi kesesuaian dan daya dukung lahan dan merumuskan strategi pengembangan sapi potong di Kabupaten Gorontalo. Data primer diperoleh dengan survei, pengamatan langsung dan wawancara (instansi dan lembaga terkait) dengan metode purposive sampling. Metode analisis yang digunakan untuk masing-masing tujuan adalah: literatur review, analisis sistem informasi Geografi (SIG), analisis SWOT. Dari hasil literatur review, pengembangan kawasan merupakan pola pengembangan yang efektif dan efesien. Hasil analisis SIG memperlihatkan kesesuaian lingkungan ekologis sapi potong mencapai 178 455 Ha (81% dari luas wilayah Kabupaten Gorontalo, potensi lahan pengembangan sapi potong terbesar yaitu Kecamatan Asparaga sebesar 11 232 ha dan indeks daya dukung hijauan makanan ternak terbesar yaitu Kecamatan Tolangohula sebesar 39,2. Dari perumusan strategi dengan SWOT diperoleh strategi penguatan perencanaan pengembangan kawasan, penguatan SDM aparat dan peternak, penguatan kelembagaan peternak, penguatan koordinasi antar instansi, penguatan sarana dan prasarana produksi, percepatan adopsi teknologi produksi, penguatan kelembagaan pemasaran dan sosialisasi pengembangan sapi potong. Kata kunci : Sapi Potong, Kesesuaian Lahan, Strategi Pengembangan Sapi Potong, Kabupaten Gorontalo